1986
DOI: 10.1128/jcm.23.5.905-910.1986
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of a Giardia lamblia-specific stool antigen (GSA 65) useful in coprodiagnosis of giardiasis

Abstract: A Giardia lamblia-specific antigen (GSA 65) was isolated from stools of G. lamblia-positive patients by crossed-and line-immunoelectrophoresis and counterimmunoelectrophoresis (CIE) in agarose by using rabbit antiserum prepared against G. lamblia cysts. CIE with rabbit anti-GSA 65 monospecific antiserum revealed that GSA 65 was present in aqueous stool eluates of giardiasis patients and in cysts and trophozoites of the parasite. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis of immunoaffinity-purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 24 publications
(18 reference statements)
1
32
0
Order By: Relevance
“…Because of this, diagnosis by microscopy is not entirely reliable (26); and there is a need for a rapid, stable, and highly sensitive assay for the detection of cell-free giardial antigens in stool specimens. Antigen-detection assays involving counterimmunoelectrophoresis (4,15,24) and antigen-capture enzyme-linked immunosorbent assay (ELISA) have previously been reported (9,11,20,23). Our previously reported polyclonal antibody-based assay (20) was 92% sensitive; prior fixation of stool specimens in 10% Formalin was found to have no detrimental effect on the ability of that assay to detect the antigen.…”
mentioning
confidence: 85%
“…Because of this, diagnosis by microscopy is not entirely reliable (26); and there is a need for a rapid, stable, and highly sensitive assay for the detection of cell-free giardial antigens in stool specimens. Antigen-detection assays involving counterimmunoelectrophoresis (4,15,24) and antigen-capture enzyme-linked immunosorbent assay (ELISA) have previously been reported (9,11,20,23). Our previously reported polyclonal antibody-based assay (20) was 92% sensitive; prior fixation of stool specimens in 10% Formalin was found to have no detrimental effect on the ability of that assay to detect the antigen.…”
mentioning
confidence: 85%
“…This procedure was done based on studies of Rosoff and collaborators (Rosoff and Stibbs, 1986). Briefly, the sediments were solved in 0.5% tween 80 solutions followed by centrifugation at 700 g for 5 min and solving and centrifugation processes were repeated periodically till the surface liquids were cleaned.…”
Section: One-phase Sucrose Gradientmentioning
confidence: 99%
“…Routine method to diagnose giardiasis is direct microscopic examination of stool (Rosoff and Stibbs, 1986;Duque-Beltran et al, 2002). Sensitivity of microscopic method even with several times repeating of each test is just 50 to 70% (Burke et al, 1975(Burke et al, , 1977.…”
Section: Introductionmentioning
confidence: 99%
“…The ELISA-GSA 65 detects a G. duodenalis-specific antigen (GSA) that is excreted in the stool. GSA has been identified in trophozoites and cysts and has an approximate molecular mass of 65 kDa (162). The ELISA-GSA 65 is available commercially as a kit, and its sensitivity and specificity are comparable to those of microscopic examination for cysts in the stool (62,163).…”
Section: Detection Of Antigens In Fecesmentioning
confidence: 99%
“…In fact, all studies with the ELISA-GSA 65 have reported a greater sensitivity of the immunodiagnosis assay over the microscopic examination of a single specimen ( Table 1). The sensitivity of the assay varies between 95 and 100%, and 100% specificity has been reported when it was used with stools from patients infected with other intestinal parasites (15,162). It has been reported that the ELISA-GSA 65 can detect Giardia infection in at least 30% more cases than the microscopic examination (163).…”
Section: Detection Of Antigens In Fecesmentioning
confidence: 99%